2012
DOI: 10.1590/s1676-06032012000200018
|View full text |Cite
|
Sign up to set email alerts
|

Crustáceos decápodos associados às cordas de cultivo do mexilhão Perna perna (Linnaeus, 1758) (Mollusca, Bivalvia, Mytilidae) na Enseada da Armação do Itapocoroy, Penha - SC

Abstract: Este estudo teve por objetivo descrever a assembleia de crustáceos decápodos associados às cordas de cultivo de mexilhões em uma fazenda marinha localizada na Enseada da Armação do Itapocoroy, no Município de Penha, Santa Catarina, sul do Brasil. Os seguintes aspectos foram tratados: composição de espécies e peso total, sucessão de espécies e oscilação temporal da abundância, riqueza de espécies e diversidade (Shannon). O crescimento do mexilhão em (altura da concha e peso dos indivíduos) também, foram apresen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…Porcellana platycheles did not manage to establish itself in São Sebastião, nor has it been recorded subsequently from elsewhere in Brazil. Macedo et al (2012) reported on 1 male and 5 females (MHNCI 3840, 3684, 3130) purportedly belonging to P. platycheles associated with mussel farming in Santa Catarina, south Brazil. However, upon examination all these specimens proved to be Pisidia brasiliensis Haig in Rodrigues da Costa, 1968.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcellana platycheles did not manage to establish itself in São Sebastião, nor has it been recorded subsequently from elsewhere in Brazil. Macedo et al (2012) reported on 1 male and 5 females (MHNCI 3840, 3684, 3130) purportedly belonging to P. platycheles associated with mussel farming in Santa Catarina, south Brazil. However, upon examination all these specimens proved to be Pisidia brasiliensis Haig in Rodrigues da Costa, 1968.…”
Section: Resultsmentioning
confidence: 99%
“…Macedo coll., 14.vii.2010, associated with Nodipecten nodosus. The above specimens were reported by Macedo et al (2012) as P. platycheles.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, in our study, we believe that the decapods established inside the box might serve as feed to the O. vulgaris Type II paralarvae, contributing to their development and survival until 14 DAH. Additionally, the ropes used in the oyster and mussel longlines provide shelter and accumulate food not only for decapod crustaceans, as reported by Macedo et al (2012), but also for a great variety and abundance of species that compound the zooplankton.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the importance of P. austrobesus as a primary consumer, especially in estuarine zones, information concerning the main features of its biology remains lacking. Except for studies related to taxonomy, composition, and geographical distribution (e.g., Melo, 1996;Vieira and Calazans, 2010;Marochi and Masunari, 2011;Alves et al, 2012a;2012b;Macedo et al, 2012), there is only a limited number of studies on the biology and ecology of P. austrobesus (see Montú et al, 1988;Negreiros-Fransozo and Fransozo, 2003). The aim of this investigation is to describe the population structure and dynamics of P. austrobesus associated with Population dynamics of Panopeus austrobesus Nauplius, 25: 2017017 P. perna mussel farms on the southeastern Brazilian coast and to compare its main characteristics to those of populations in their natural environments.…”
Section: Introductionmentioning
confidence: 99%